Spatial planning and electric vehicles. A qualitative case study of horizontal and vertical organisational interplay in southern Sweden. Issue 8 (3rd July 2018) - Antonson, Hans; Carlson, Annelie
Abstract : The use of electric-powered vehicles (EV) is experiencing a boom in some countries. Much research has been conducted on the technology per se; however, there is a research gap regarding institutional spatial planning practice concerning EVs. Here, an empirical analysis was made of planners' interpretations of opportunities and obstacles to integration of EVs in southern Sweden. The results revealed a lack of interplay between local and regional administrations and showed that the agenda is run by individual bureaucrats rather than being based on official strategies. Moreover, there appears to be a lack of horizontal interplay within some organisations, while new arenas are being formed by actors within and outside government. The reason for formation of such external EV networks may be a single actor not being able to push the issue forward alone, due to a fragmented organisation, or a lack of clear external task formulation at central government level.